PRODUCT AUTHENTICATION USING QR CODE WITH THE HELP OF RSA ALGORITHM - Kumar, Pankaj; Raghav, Kumar (International Journal of Psychosocial Rehabilitation, 2024)
The advent of online shopping has led to a surge in ecommerce websites offering products from wellknown brands at very competitive prices. However, the cases of fake products and duplicity have alsoseen an increase in recent years, because of lack of proper mechanism to ensure authenticity of theproducts, whether purchased online or from a physical shop. In spite of the availability of a number oftechniques and technology, there is still no means to check the delicacy occurring due to copyingproduct information and generating fake QR codes, barcodes etc and using on fake or duplicateproducts. In this paper, we propose a methodology for product authentication by using the RSAalgorithm on QR code. RSA involves a public key and private key. The public key can be known toeveryone- it is used to encrypt messages. Messages encrypted using the public key can only bedecrypted with the private key.